Description and distribution of Helminth parasites of White-bellied Grass mice (Akodon albiventer) and Andean Vesper mice (Calomys lepidus) of the altiplano region of Bolivia - Griffin, Bretton Skyler, author; Moore, Janice, advisor; Black, William, committee member; Raines, Karen, committee member (Colorado State University. Libraries, 2016)
Akodon and Calomys genera are among the most speciose of South American rodents. Within Bolivia, these genera inhabit multiple environments of varied geomorphology, elevation, vegetation and climates, including the Bolivian altiplano, which consists of complex ecosystems at elevations of 3,000 meters and above. A number of species like the White-Bellied Grass Mouse (Akodon albiventer) and Andean Vesper Mouse (Calomys lepidus) primarily reside at the high elevations of the altiplano. Because of their habitat location, relatively few studies have addressed A. albiventer and C. lepidus parasites, specifically their helminth parasites. To gain further knowledge about the parasite fauna infecting these rodents, a biodiversity survey was conducted. This biodiversity survey is the first that describes and reports the distribution of helminth parasites occurring in A. albiventer and C. lepidus collected from the altiplano region of Bolivia. Gardner and colleagues collected A. albiventer and C. lepidus hosts during expeditions in 1984-1993 from five departments in Bolivia: Oruro, Chuquisaca, Tarija, La Paz, and Cochabamba. From these collections, 27 A. albiventer and 11 C. lepidus were randomly chosen for parasite analysis, and yielded a total of 702 helminth parasite specimens, representing five helminth taxa. Oxyurids were the most common, followed by protospirurids, rictulariids, trichostrongylids, and cestodes. These are the first parasite records from A. albiventer and C. lepidus within the altiplano region of Bolivia. Many of the oxyurid parasites recovered from A. albiventer and C. lepidus were unidentifiable to species due to the overlap of morphological measurements and features. In order to evaluate the accuracy of manual identification techniques through the examination of morphological relationships between species, statistical analyses were performed on male and female oxyurid specimens (Syphacia spp.) separated into three species groups. The analyses indicated that two species groups from the host, A. albiventer, shared more morphological measurement similarities than the species group from C. lepidus. Though further analysis is necessary, it is possible that the species group derived from C. lepidus is a new Syphacia species.
Keywords: Calomys lepidus; Akodon albiventer; helminth; Bolivia; altiplano